2017
DOI: 10.24200/sci.2017.4444
|View full text |Cite
|
Sign up to set email alerts
|

A capital flow constrained lot sizing problem with trade credit

Abstract: Abstract. This paper incorporates capital flow constraints and trade credit to lot sizing problems. Capital flow constraint is different from traditional capacity constraints: when a manufacturer begins to produce a certain number of products, its present capital should not be less than its total production costs of that period; otherwise, the manufacturer must decrease production quantity or suspend production, or it could delay payment using trade credit. Moreover, the capital of each period should also be g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…This is particularly important in the context of lot sizing problems, where finding the global optimum is crucial for efficient production planning and goods flow control [73]. Additionally, GAs have been applied to solve single-item lot sizing problems with immediate lost sales in profit maximization models, demonstrating their versatility in addressing different variations of lot sizing problems [74]. optimization problems [75].…”
Section: Solution Approach-based Genetic Algorithmmentioning
confidence: 99%
“…This is particularly important in the context of lot sizing problems, where finding the global optimum is crucial for efficient production planning and goods flow control [73]. Additionally, GAs have been applied to solve single-item lot sizing problems with immediate lost sales in profit maximization models, demonstrating their versatility in addressing different variations of lot sizing problems [74]. optimization problems [75].…”
Section: Solution Approach-based Genetic Algorithmmentioning
confidence: 99%
“…Chen and Zhang [20] incorporated capital flow constraints and trade credit to lot-sizing problems. They formulate a mathematical model for this problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…20) represent that if the setup of product i of family j has occurred and product i is first or single product of family j in level z and during period t then…”
mentioning
confidence: 99%
“…(2018) investigated the working capital requirement and demonstrated that the zero‐inventory‐ordering property remains valid in this problem. Chen and Zhang (2018) discussed a cash‐constrained lot‐sizing model with trade credit.…”
Section: Literature Reviewmentioning
confidence: 99%